From amaurotic idiocy to biochemically defined lipid storage diseases: the first identification of GM1-Gangliosidosis - Kasper, Burkhard S.; Thomas, Christian; Albers, Anne; Kasper, Ekkehard; Sandhoff, Konrad (Free Neuropathology, 2023)
On February 23rd 1936, a boy-child (“Kn”) died in an asylum near Munich after years of severe congenital dis-ease, which had profoundly impaired his development leading to inability to walk, talk and see as well as to severe epilepsy. While a diagnosis of “Little’s disease” was made during life, his postmortem brain investiga-tion at Munich neuropathology (“Deutsche Forschungsanstalt für Psychiatrie”) revealed the diagnosis of “amaurotic idiocy” (AI). AI, as exemplified by Tay-Sachs-Disease (TSD), back then was not yet understood as a specific inborn error of metabolism encompassing several disease entities. Many neuropathological studies were performed on AI, but the underlying processes could only be revealed by new scientific techniques such as biochemical analysis of nervous tissue, deciphering AI as nervous system lipid storage diseases, e.g. GM2-gangliosidosis. In 1963, Sandhoff & Jatzkewitz published an article on a “biochemically special form of AI” reporting striking differences when comparing their biochemical observations of hallmark features of TSD to tissue composition in a single case: the boy Kn. This was the first description of “GM1-Gangliosidosis”, later understood as resulting from genetically determined deficiency in beta-galactosidase. Here we present illus-trative materials from this historic patient, including selected diagnostic slides from the case “Kn” in virtual microscopy, original records and other illustrative material available. Finally, we present results from genetic analysis performed on archived tissue proving beta-galactosidase-gene mutation, verifying the 1963 interpre-tation as correct. This synopsis shall give a first-hand impression of this milestone finding in neuropathology.